SEMANTICALLY IMPLIED IRREGULAR INFLECTION. - Deibler, Scott (International Social Science Review, 2012)
The article presents information and results from a study regarding the inflection and pronunciation of words and the manipulation of semantic information in order to imply irregularity. The author explains his use of Old English words to avoid familiarity of inflection with more commonly used words, explores how his study fits into the existing psycholinguistic research pertaining to how the human brain processes language, and presents his findings, which indicate that language is processed in a generalized way, much like most other information.